Performance of 19-year-old provenances of Liquidambar styraciflua in Paraguaçu Paulista, São Paulo - Sebbenn, Alexandre Magno (2007)
The genetic variation in the growth of seven 19-year-old Liquidambar styraciflua provenances was studied in Paraguaçu Paulista, São Paulo State, Brazil. The trial was established in a complete randomized block design with seven provenances, four replications and twelve-tree square plots. Significant differences among provenances were detected for diameter at breast height, height and volume, indicating the possibility of increasing timber yield through selection of the most productive provenances. Genetic correlations between growth traits were high and statistically significant. The provenance from Finca las Victorias, Guatemala had the best and the provenance from Franklin, Virginia, United States the poorest performance for all traits. A growth comparison of Pinus caribaea var. bahamensis with the best provenance at the same site indicated that the potential of L. styraciflua for silviculture in the region of Paraguaçu Paulista is high.